Retrograde Totally Endovascular Recanalization of Occluded Mesenteric Arteries Through the Pancreaticoduodenal Arcade. (2015) - Asciutto, G.; Sonesson, B.; Björses, K.; Kristmundsson, T.; Resch, T.; Dias, N.V.
Abstract : Introduction: Failed antegrade endovascular recanalization of occluded mesenteric arteries has traditionally been dealt with by open mesenteric bypass or by hybrid solutions. This article describes a totally endovascular retrograde approach for recanalization of occluded mesenteric arteries through the pancreaticoduodenal arcade. Surgical technique: A femoral or brachial approach is used to gain access to the patent visceral artery. A micro-catheter is advanced in a retrograde fashion into the distal main stem of the occluded artery through the gastroduodenal artery and inferior pancreaticoduodenal arcade. A combination of .014″ and .018″ wires is used to cross the occlusion in a retrograde fashion and to land into the aortic lumen. The guide wire is then snared through the brachial access, establishing a through and through wire. A micro-catheter is then advanced on the through and through wire across the occlusion from the brachial access. The distal occluded artery is then catheterized by advancing a second wire parallel to the through and through wire. The remaining procedure is performed as a standard antegrade approach. Discussion: The totally endovascular retrograde approach through collaterals can be helpful for the recanalization of mesenteric artery occlusions. This technically complex procedure should be reserved for cases in which the traditional antegrade approach has failed.